Situation and determinants of the infant and young child feeding (IYCF) indicators in Madagascar: analysis of the 2009 Demographic and Health Survey - Hasina Rakotomanana; Gail E. Gates; Deana Hildebrand; Barbara J. Stoecker (BMC, 2017)
Abstract Background Studies evaluating child feeding in Madagascar are scarce despite its importance in child growth during the first two years of life. This study assessed the associations between the WHO infant and young child feeding (IYCF) indicators and stunting and identified determinants of inappropriate child feeding practices. Methods The most recent Demographic and Health Survey was used including a total of 1956 infants aged 0-23 months. Logistic regressions were performed for the association between IYCF indicators and stunting and for the determination of risk factors for inappropriate feeding practices. Results The rates of initiation of breastfeeding within one hour after birth (77.2%), continued breastfeeding at one year (99.6%) and timely introduction of solid, semi-solid or soft foods at 6-8 months (88.3%) were high. Exclusive breastfeeding under 6 months (48.8%), attaining minimum dietary diversity (22.2%) and consumption of iron-rich foods (19.6%) were relatively low. Higher length-for-age was associated with achieving minimum dietary diversity (p<0.01). The other indicators assessed (early initiation of breastfeeding, exclusive breastfeeding under 6 months, timely introduction of complementary foods and consumption of iron-rich foods) were not associated with stunting. Infants born to mothers who had first given birth at an age younger than 19 were more likely not to be breastfed within one hour after birth, not to be exclusively breastfed and not to have the recommended dietary diversity. Infants whose mothers had low media exposure were at increased risk of being inappropriately fed. Low household wealth also was associated with higher odds of not meeting the minimum dietary diversity. Conclusions Despite almost total continued breastfeeding at one year and early initiation of breastfeeding by more than three-quarter of mothers, minimum dietary diversity scores were still low, confirming the need for more effective programs for improving child feeding practices in Madagascar. Improving dietary diversity in children aged 6-23 months may help reduce stunting. The identified risk factors for inappropriate feeding practices could be used in directing future nutrition sensitive interventions.